“Aqui o pessoal pensa assim” etnia, parentesco e negócios em um morro de Porto Alegre - Ribeiro, Marco Antônio Andrade (2020)
This dissertation is the result of an anthropological research of an ethnographic nature carried out between 2014 and 2018 in Morro da Cruz, São José neighborhood, Porto Alegre, RS. The main focus of this work is the economic relations inserted in the social context of families of entrepreneurs in a poor neighborhood. The economic daily life of the different agents is marked by different ties, ethnic ties, parenting and neighborhood relations that are part of the tangle between personal life and business. In this sense, different capitals, agents and institutions that make up the local economic arrangements are activated. The fieldwork involved different levels of participatory observation, including the participation of the researcher in a local business and the relationships between residents and the “outsiders” (people who work for different reasons in Morro) are decisive in the construction of new paths for local entrepreneurs.